Biochemical, Antioxidant Properties and Antimicrobial Activity of Epiphytic Leafy Liverwort Frullania dilatata (L.) Dumort - Simsek, Ozcan; Canli, Kerem; Benek, Atakan; Turu, Dilay; Altuner, Ergin Murat (MDPI AG, 2023)
In this study, the biochemical, antioxidant properties, and antimicrobial activity of the epiphytic leafy liverwort Frullania dilatata (L.) Dumort were investigated. Due to the scarcity and difficulty in obtaining liverworts, research on their bioactivity is limited; thus, this study aimed to uncover the potential of F. dilatata. The antimicrobial activity was evaluated against various microorganisms, including food isolates, clinical isolates, multidrug-resistant strains, and standard strains, using the disk diffusion method and determining the minimum inhibitory concentration (MIC) values. This study represents the first antioxidant investigation on F. dilatata and an antimicrobial study using ethanol extract and the disk diffusion method. Notably, susceptibility was observed in Enterococcus faecalis ATCC 29212, Enterococcus faecium FI, Listeria monocytogenes ATCC 7644, Providencia rustigianii MDR, and Staphylococcus aureus ATCC 25923. The antioxidant capacity was assessed using the DPPH method, emphasizing the high scavenging performance. Gas chromatography-mass spectrometry (GC-MS) analysis identified the primary compounds as frullanolide (19.08%), 2,3-Dimethylanisole (15.21%), linoleic acid (11.11%), palmitic acid (9.83%), and valerenic acid (5.3%). The results demonstrated the significant antimicrobial activity of F. dilatata against the tested microorganisms and its potent antioxidant properties. These findings emphasize the potential of F. dilatata as a promising source of natural antimicrobial and antioxidant agents, underscoring the importance of further investigation into its bioactive compounds and elucidating the mechanisms of action in future studies.
Keywords: antimicrobial activity; bioactive compounds; Frullania dilatata; QK1-989; Botany; antimicrobial activity; antioxidant properties; bioactive compounds; Frullania dilatata; liverworts; antioxidant properties; liverworts; Article; 3. Good health